Nurses Monitor Medication with a Schedule for Undrop-Out Program (SRAGAM) for TBC Clients - Andi Rinaldo; Aprina Aprina (Jurnal Kesehatan)
Regulation Minister of Health Republic Indonesia Number 15 of 2022 through 6 pillars of health transformation, one of which is primary service, namely medication adherence education. Ministry of Health Republic Indonesia, (2020) the 2020-2024 RPJMN policy directions and Sustainable Development Goals (SDGs) regarding six diseases, one is Tuberculosis (TBC). TBC prevalence in Southeast Asia (44%), Indonesia (8.5%), Lampung (40.2%), and South Lampung (41%). Indonesia's strategy to reduce the incidence of TBC has six plans: the 2020-2024 national tuberculosis program, optimizing promotion and prevention efforts, providing tuberculosis prevention treatment, and controlling. TBC treatment 6-24 months resulted in drop-out treatment. Nurses play a supervisory role and carry out counseling to increase patient adherence. The Schedule For Undrop-Out Program (SRAGAM) is a media innovation to improve patient medication adherence. SRAGAM makes it easier for patients, PMOs, and health workers to arrange medication-taking schedules. The purpose is to determine the effect of SRAGAM on increasing patient adherence. Research is a quantitative one-group pretest-posttest with a control group preexperimental design. Respondents were patients who were taking drugs. The number of samples was 32 respondents (16 intervention:16 control). The research was from December 2022 to May 2023 in Hajimena Health Center, South Lampung. Data analysis using t-test. The results of the study mean value intervention group (5.6875) and control group (4.1250). The P-value of 0.000 concluded that SRAGAM effectively increased the number of patients taking medication. The results will become educational media in preventing the incidence of dropping medication in patients.